2009
DOI: 10.1029/2009jd012029
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of large peak current cloud‐to‐ground lightning flashes in southeastern Brazil

Abstract: [1] The goal of this article is to present the first climatology of large peak current cloud-toground (LPCCG) flashes in southeastern Brazil, in terms of flash density, percentage of positive LPCCG flashes, peak current, and diurnal distributions. The results are based on data provided by the Brazilian Lightning Detection Network (BrasilDat) from 1999 to 2006, and only flashes with peak currents >75 kA recorded during the months of December, January, February, and March (the approximate summer season in the So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 34 publications
2
19
1
1
Order By: Relevance
“…this value is lower than the values calculated from observations by Lyons et al (1998a) and Pinto et al (2009), 5.4 and 2.8, respectively. Negative LCLFs in Canada are less numerous for peak currents > 200 kA (average ratio of 0.6), compared to the findings of Lyons et al (1998a) and Pinto et al (2009), 4.1 and 1.1, respectively. LCLFs with stroke multiplicity ≥10 are primarily associated with negative CG flashes and detected in all seasons except winter (table 2).…”
Section: Multiplicity Multiplicitycontrasting
confidence: 43%
“…this value is lower than the values calculated from observations by Lyons et al (1998a) and Pinto et al (2009), 5.4 and 2.8, respectively. Negative LCLFs in Canada are less numerous for peak currents > 200 kA (average ratio of 0.6), compared to the findings of Lyons et al (1998a) and Pinto et al (2009), 4.1 and 1.1, respectively. LCLFs with stroke multiplicity ≥10 are primarily associated with negative CG flashes and detected in all seasons except winter (table 2).…”
Section: Multiplicity Multiplicitycontrasting
confidence: 43%
“…However, for the positive LPCCG lightning, two high-concentration regions, one around the mouth of the Pearl River and the other to the north of the Leizhou Peninsula, are connected by a belt of scattered high-density lightning locations. Differences between positive and negative LPCCG lightning densities have also been reported by Lyons et al (1998) and Pinto et al (2009). Table 2 lists the average lightning density over land and offshore regions, including the ratios of the average density over land to that over water.…”
Section: Spatiotemporal Characteristics Of Lightning Activitymentioning
confidence: 61%
“…In previous studies (e.g., Cummins et al, 1998), positive CG (PCG) lightning flashes with currents of <10 kA were removed from the data as they might be a misinterpretation of cloud lightning. Furthermore, following the subjective definition of Lyons et al (1998) and Pinto et al (2009) of LPCCG lightning, the CG lightning with an absolute peak (Lyons et al, 1998), and a ratio of 3% has been reported over southeastern Brazil (Pinto et al, 2009). High Resolution Full Climatology TRMM/Lightning Imaging Sensor (LIS) 0.5 • data were used to determine the total lightning activity in the study region.…”
Section: Data and Their Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Lightning has been the object of many studies since the end of the nineteenth century, beginning with recordings using still cameras [ Hoffert , 1888], followed by the use of time‐resolved photography, instrumented towers, video cameras, lightning locating and mapping systems, triggered lightning facilities, and, more recently, satellite optical sensors. Lightning characteristics based on these techniques have been published by many authors [e.g., Rakov et al , 1994; Diendorfer et al , 1998, 2002; Valine and Krider , 2002; Pinto et al , 2003; Rakov and Huffines , 2003; Schulz et al , 2005; Hussein et al , 2006; Miki et al , 2006; Pinto et al , 2006; Biagi et al , 2007; Pinto et al , 2007; Flache et al , 2008; Pinto et al , 2009]. Recently, high‐speed video cameras have added much to our understanding of natural downward lightning physics [e.g., Ballarotti et al , 2006; Kong et al , 2008; Saba et al , 2008; Campos and Saba , 2009; Saba et al , 2009].…”
Section: Introductionmentioning
confidence: 99%